Pressure-induced superconductivity in CrAs and MnP. (18th August 2017) - Cheng, Jinguang; Luo, Jianlin
Abstract: Transition-metal monopnictides, CrAs and MnP, were studied over 50 years ago due to the presence of interesting magnetic properties: CrAs forms a double-helical magnetic structure below T N   ≈  270 K accompanied by a strong first-order structural transition, while MnP first undergoes a ferromagnetic transition at T C   ≈  290 K and then adopts a similar double-helical order below T s   ≈  50 K. Both compounds are correlated metals and exhibit distinct anomalies at these characteristic magnetic transitions. By using high pressure as a clean tuning knob, we recently observed superconductivity with a maximum superconducting transition temperature of T c   ≈  2 K and 1 K when their helimagnetic orders are suppressed under a critical pressure of P c   ≈  0.8 and 8 GPa for CrAs and MnP, respectively. Despite a relatively low T c, CrAs and MnP are respectively the first superconductor among the Cr- and Mn-based compounds in that the electronic density of states at the Fermi energy are dominated by Cr/Mn-3d electrons. These discoveries, in particular the close proximity of superconductivity to the helimagnetic order reminiscent of many unconventional superconducting systems, have attracted considerable attention in the community of superconductivity. The evolution of the helimagnetic order under pressure and its relationship with superconductivity have been actively investigated recently. Much effort has also been devoted to exploring more novel Cr- or Mn-based superconductors, leading to the discovery of quasi-1D A2 Cr3 As3 (A  =  K, Rb, Cs) superconductors. In this review article, we will summarize the current progress achieved regarding superconductivity in CrAs and MnP.